Correlated environmental DNA and electrofished estimates of relative biomass for golden perch, Macquaria ambigua - Rourke, Meaghan L.; Broadhurst, Matt K.; Fowler, Ashley M.; Hughes, Julian M.; DiBattista, Joseph D.; Furlan, Elise M. (Frontiers in Fish Science, 2024)
In response to a need to augment electrofishing surveys of golden perch, Macquaria ambigua (an important endemic freshwater fish in southeastern Australia) with other nonlethal, survey methods, the utility of environmental (eDNA) as an index of relative fish abundance/biomass was investigated. Five sites in each of three adjacent rivers were sampled for eDNA immediately prior to electrofishing during two sequential years. Up to six individuals or 10 kg of electrofished golden perch (200-548 mm total length) were caught/observed site -1 . Analyses of concurrent eDNA concentrations revealed no significant relationship with the relative abundance of golden perch, but there was with relative biomass-manifesting as increasing eDNA concentrations between 1.1 and ~5.5 kg biomass site -1 , after which concentrations stabilised at greater biomasses. Future research warrants assessing the viability of sampling eDNA for spatio-temporally monitoring rivers where low biomasses of golden perch (1-5 kg site -1 ) are likely to occur.